微分方程xy'=2y满足初始条件y|x=1=3的解是()。
A: y=x2+2
B: y=3x2
C: y=cx2
D: y=x2+c
A: y=x2+2
B: y=3x2
C: y=cx2
D: y=x2+c
举一反三
- 方程\(\left( {1 - {x^2}} \right)y - xy' = 0\)的通解是( )。 A: \(y = C\sqrt {1 - {x^2}} \) B: \(y = - {1 \over 2}{x^3} + Cx\) C: \(y = {C \over {\sqrt {1 - {x^2}} }}\) D: \(y = Cx{e^{ - {1 \over 2}{x^2}}}\)
- 下列函数中,( )不是方程\( xy' + y - x^2 = 0 \)的解。 A: \( y = { { {x^2}} \over 3} + {1 \over x} \) B: \( y = { { {x^2}} \over 3} \) C: \( y = { { {x^2}} \over 3} + 2 \) D: \( y = { { {x^2}} \over 3} - {1 \over x} \)
- 下列方程中( )是微分方程。 A: \( x{y^3} + 2{y^2} + {x^2}y = 0 \) B: \( {y^2} + xy - y = 0 \) C: \( x + {y^2} = 0 \) D: \( dy + ydx = 0 \)
- 分解因式()x()3()y()-()2()x()2()y()2()+()xy()3()正确的是A.()xy()(()x()+()y())()2()B.()xy()(()x()2()﹣()2()xy()+()y()2())()C.()xy()(()x()2()+2()xy()﹣()y()2())()D.()xy()(()x()﹣()y())()2
- 设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)